Linking entrepreneurial orientation and small service firm performance through marketing resources and marketing capability: A moderated mediation model - Sok, P.; Snell, L.; Lee, Thomas; Sok, K. (Emerald Group Publishing, 2016)
Purpose: The literature establishes complex relationships between entrepreneurial orientation (EO) and performance, with mixed findings suggesting the variability of the magnitude of the relationship between the two. Some studies report a positive relationship, some negative, while some report an insignificant relationship between EO and performance. These conflicting findings suggest that the EO-performance relationship is more complex than a simple main-effects-only relationship. The literature offers two distinct approaches – integrating moderating or mediation variables in advancing the EO-performance relationship. The purpose of this paper is to extend current knowledge by examining underlying processes through which EO contributes to performance and the specific conditions under which this process is facilitated. Design/methodology/approach: To test the hypotheses the authors chose small service firms in Australia. Industry representation included: accommodation and food services; health care services; rental, hiring and real estate services; transport, postal and warehousing; arts and recreation services; retail trade; construction and training services; and professional, scientific and technical services. The services sector offers a unique opportunity to analyze variances in entrepreneurial engagement and organizational outcomes given the competitive intensity within the service sector which requires firms to engage in venturing, renewal and innovation. The proposed hypotheses were tested through a hierarchical regression analysis. Findings: This study finds the support for the mediation effect of marketing capability on the EO-performance relationship. Critically, this study also finds that marketing resources moderates on the indirect effect of EO on performance via marketing capability. The findings supporting both the mediation and moderation effects of marketing capability and marketing resources on the EO-performance relationship (moderated mediation model) suggests that greater insight into how EO influences small service firm performance can be achieved through considering in combination with other firm-level constructs (marketing capability and marketing resources in this study). Originality/value: It addresses the call by prior studies to link the EO construct to theory by embedding marketing resources and marketing capabilities in the EO-performance relationship. Importantly, by accounting for both mediation and moderation effects the authors provide a more complete picture of the EO-performance relationship that highlights the mediating role of marketing capability and the moderating role of marketing resources. This approach helps to reconcile the critical but separate directions proposed by prior studies in advancing the EO-performance relationship.